Greening the Campus: Strategies for Sustainable Transformation in Higher Education - Doris Chasokela (Journal of Education for Sustainable Development Studies, 2025)
This article investigates strategies for achieving sustainable transformation within higher education, specifically centered on ‘Greening the Campus.’ As environmental challenges intensify, universities are pivotal in promoting sustainable practices across their operations and educational frameworks. This study highlights successful initiatives implemented by various institutions, particularly within engineering disciplines, showcasing best practices while addressing the challenges faced and the overall effects on campus culture and community engagement. Utilising a mixed research approach, which includes a thorough literature review and case studies of universities recognised for their sustainability efforts, we identify several key strategies. The study is a case study of the electrical and mechanical engineering departments, and 30 students and 10 lecturers were sampled. These include increasing energy efficiency, encouraging sustainable transportation solutions, and infusing sustainability principles into engineering curricula. Findings reveal that institutions prioritizing sustainability not only minimise their ecological footprint but also cultivate a heightened sense of awareness and responsibility among students and staff. Furthermore, the discussion emphasises the critical role of leadership commitment and active stakeholder involvement in advancing sustainable initiatives, particularly within engineering programs. The conclusion advocates for a comprehensive approach to sustainable transformation, urging higher education institutions to embed these strategies within their culture and curricula. By doing so, universities can contribute meaningfully to global sustainability objectives while preparing students to tackle pressing environmental challenges. The overarching message is clear: a commitment to greening the campus fosters an environment that not only supports ecological stewardship but also inspires the next generation of engineers and leaders to face global sustainability challenges head-on.